Sesquiterpenes and sterols from the soft coral Sinularia cruciata - Tung, Pham The; Mai Huong, Pham Thi; Huong, Tran Thu; Thung, Do Cong; Thanh, Nguyen Van; Tuan Anh, Hoang Le; Nam, Nguyen Hoai; Cuong, Nguyen Xuan; Kiem, Phan Van; Minh, Chau Van (Vietnam Journal of Chemistry, 2015)
Two sesquiterpenes as sinularianin D (1) and 1S*,4S*,5S*,10R*-4,10-guaianediol (2), and three sterols as 24-methylenecholestane-3β,5α,6β-triol-6-monoacetate (3), 3β,7α-dihydroxyergosta-5,24(28)-diene (4), and 3β-hydroxyandrost-5-ene-17-one (5), were isolated from a methanol extract of the soft coral Sinularia cruciata. Their structures were elucidated by 1D and 2D-NMR experiments and comparison of their NMR data with reported values. This is the first report of these compounds from S. cruciata